2018
DOI: 10.1159/000490065
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Accident Risk in a Population with Periodic Limb Movements of Sleep: A Preliminary Meta-Analysis

Abstract: Background and Purpose: Periodic limb movements of sleep (PLMS) are usually comorbid with hypertension, tachycardia, and coronary arterial diseases, which are also risk factors for cerebrovascular accidents (CVA). However, evidence about the relationship between CVA and PLMS is still weak. The aim of this study was to investigate (1) the prevalence of CVA in patients with PLMS, and (2) the severity of PLMS in patients with or without CVA through a meta-analysis. Methods: The electronic databases of PubMed, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Systematic reviews: Two systematic reviews on RLS including 18 studies and eight studies, respectively, were considered [101,102]. For PLMS there is a recent systematic review that included five studies [103]. The original studies included in the systematic review were of class II and III quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews: Two systematic reviews on RLS including 18 studies and eight studies, respectively, were considered [101,102]. For PLMS there is a recent systematic review that included five studies [103]. The original studies included in the systematic review were of class II and III quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Systematic reviews: A recent systematic review of three studies on PLMS was included [103]. The original studies included in the systematic review were of class II and III quality.…”
Section: Results Of Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Overview of the evidence. The meta-analysis evaluated 158 PLMS patients with stroke and 88 PLMS patients without stroke from three studies [103]: a higher PLMI was found in stroke patients (Hedges' g = 0.860, mean difference 4.43) (Table S20).…”
Section: Is the Frequency Of Rls/plms Increased In Stroke Patients?mentioning
confidence: 99%
“…[1][2][3] Sleep impairment and poor sleep, in addition to being secondary symptoms of diseases such as stroke, can result from diagnosable (and treatable) sleep disorders such as obstructive sleep apnea, insomnia disorder, and restless legs syndrome. The strokesleep literature has focused primarily on obstructive sleep apnea, known to be both a risk factor and consequence of stroke, [4][5][6][7][8][9][10] and to negatively impact functional outcomes after stroke. 11,12 Insomnia is also problematic in persons with stroke, according to a recent meta-analysis that found insomnia diagnoses and insomnia symptoms are more prevalent in persons following stroke than in the general population.…”
Section: Introductionmentioning
confidence: 99%